Improving Self-Management and Controlling Blood Pressure in Hypertensive Elderly Groups with the RENJANA Program: Meningkatkan Manajemen Diri dan Mengontrol Tekanan Darah Kelompok Lansia Hipertensi dengan Program RENJANA (Relaksasi Genggam Jari dengan Nafas Dalam) - Sari, Ni Luh Putu Dian Yunita; Martini, Ni Made Dwi Ayu; Prastikanala, I Kadek (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertensive elderly are very susceptible to blood pressure fluctuations despite taking regular medication. This phenomenon occurs in the hypertensive elderly group in the partner area. This programme offers education related to hypertension as well as hands-on demonstration of ‘Renjana’ deep breath and finger grip relaxation. Monitoring of the programme was conducted for a month to measure the level of self-management of hypertension in the elderly. Meanwhile, blood pressure was evaluated directly before and after the intervention of finger grip relaxation and deep breathing. The results obtained were a decrease in the average systolic and diastolic blood pressure, and an increase in the level of elderly self-management of hypertension. These results are expected to be a guideline for health workers holding elderly and non-communicable disease programmes to control the blood pressure of hypertensive elderly by improving self-management that emphasises stress reduction efforts.